2022
DOI: 10.1155/2022/8494734
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Repairing Tendon and Ligament Injury of Wushu Athletes by Medical Image

Abstract: Medical imaging can be used as a medical aid for diagnosis and treatment, and color Doppler ultrasound can also be used in life science research as a scientific research method. Wushu is a traditional sport in China, which has a long history of development. Martial arts are a very good fitness project, but different from ordinary people, professional martial arts athletes are often accompanied by a variety of sports injuries, and tendon ligament injury is one of the most common injuries. At present, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Fisher's exact test was used for comparisons between styles, with a Bonferroni correction for multiple comparisons. There is also research by Shi et al (2022) that has studied the Effect of Repairing Tendon and Ligament Injuries of Wushu Athletes by Medical Image. This research is related to the paper will take this as the main research purpose for an in-depth study.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher's exact test was used for comparisons between styles, with a Bonferroni correction for multiple comparisons. There is also research by Shi et al (2022) that has studied the Effect of Repairing Tendon and Ligament Injuries of Wushu Athletes by Medical Image. This research is related to the paper will take this as the main research purpose for an in-depth study.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%